Life Cycle Cost Analysis in Flat Buildings (Case Study of Polresta Bukittinggi Flat Construction Project) - Febrianti, Sri Suci; Giatman, Muhammad (CIVED, 2024)
The housing crisis in various cities in Indonesia has become an increasingly urgent issue. Rapid population growth and urbanization are major factors contributing to this crisis. One proposed solution is the development of high-rise building projects as a more practical and space-saving housing solution. However, in the context of high-rise construction, economic planning is crucial to ensure project sustainability. This research utilizes a quantitative method with secondary data collection. Life Cycle Cost (LCC) analysis is employed to control project costs from the initial stage to project completion, including construction, operational, maintenance, and demolition costs. The analysis results indicate that initial construction costs, operational costs, maintenance costs, and demolition costs all need to be considered in project planning. Maintenance and upkeep costs are crucial aspects in ensuring the building's sustainability throughout its economic life. By considering all these factors, the total life cycle cost of the construction of Rusun Polresta Bukittinggi during its operational period of 50 years amounts to Rp 32,064,519,750.22. The Annual Equivalent (AE) analysis shows an average annual cost of is Rp. 6,287,507,789.17.